EFFECTS OF β -CARIOFYLENE OF PIPER NIGRUM EXTRACT IN THE SPERM HYPERACTIVATION AND IN THE FERTILIZING CAPACITY OF THE BLACK SEA URCHIN, TETRAPYGUS NIGER (MOLINA, 1782) - Zapata, Daniela (2019)
We analyzed hyperactivation and fertilizing capacity of the sperm of Tetrapygus niger "black sea urchin" in the presence of β-caryophyllene. β-caryophyllene obtained from extracts of Piper nigrum "black pepper" and synthetic β-caryophyllene donated by the Biosciences Institute of the University of Sao Paulo, Sao Paulo, Brazil, was used. Tetrapygus niger spermatozoa pretreated with the extracts of synthetic β-caryophyllene (β-caryophyllene A) and β-Caryophyllene from black pepper (β-caryophyllene B) were used to study the effect of this molecule on sperm hyperactivity (mean velocity and percentages of progressive and continuous movement) and the fertilizing capacity (percentage of fertilized ovules). The average values ​​of the sperm head area in the control and in the treatments with β-caryophyllene A and β-caryophyllene B were: 33.8; 32.33 and 33.59 um2, respectively, indicating the homogeneity in the sample and that this was not influenced by the sesquiterpene. In the presence of β-caryophyllene A and B, the average speed observed was decreased by approximately 30 and 20 um/s, respectively, with respect to the control. There are significant differences between the control and the treatments with β-caryophyllene A and B, but not between the two treatments with β-caryophyllene. The progressive movement of the sperm was also affected. While all the sperm of the control group showed rapid progressivity; in the treatment with β-caryophyllene B only 40% presented this characteristic and in the treatment with β-caryophyllene A 100% were progressive slow. On the other hand, the β-caryophyllene B produced a slight decrease in fertilization (96.76% of fertilized ovules) and in the presence of β-caryophyllene A, this was reduced to 79.50% with respect to the control group. A possible mechanism to explain the effects observed in this study would be the ability of β-caryophyllene to activate inhibitory G proteins as reported in other studies.